The effect of paddles on pressure and force generation at the hand during front crawl - Tsunokawa, T.; Tsuno, T.; Mankyu, H.; Takagi, H.; Ogita, F. (Human Movement Science, 2018)
Through pressure measurement, this study aimed to clarify the effects of hand paddle use on pressure and force generation around the hand during the front crawl. Eight male swimmers performed two trials of front crawl swimming with maximal effort, once using only their hands and once aided by hand paddles. During trials, pressure sensors and underwater motion capture cameras were used together to analyze hand kinematics and pressure forces acting on the hand. Six pressure sensors were attached to the right hand, and pressure forces acting on the right hand were estimated by multiplying the areas and the pressure differences between the palm side and dorsal side of the hand. Acting directions of pressure forces were analyzed using a normal vector perpendicular to the hand, calculated from coordinates of the right hand. As a result, using hand paddles decreases pressure differences between the palm and dorsal sides of hand related to the magnitude of pressure force. However, no difference was found in the mean value of resultant pressure forces compared with using hands alone, because the large surface area of the hand paddle compensated the decreased pressure differences due to decreased hand velocity. In addition, when hand paddles were used, the component of the pressure force acting in propulsive direction was significantly higher. Thus, the ratio of forces acting in the propulsive direction was higher than without hand paddles. These results suggest that the training loads with hand paddles are not high even if the swimming velocities increase because the power generated by upper limb motion didn`t increase. AUTORREFERAT